Time and Crack Length Dependent Stochastic Models of Fatigue Crack Growth. State-of-the-Art Review - Doliński, K. (Engineering Transactions, 1992)
Random character of fatigue crack growth observed in experiments inspires many researchers to apply the methods of probability theory and theory of stochastic processes in modeling of the phenomenon. Among many proposals the continuous stochastic models seen to be very promising both in theoretical consideration and engineering applications. In the paper two concepts of this kind of modeling are presented: the time and crack length dependent models. Some advantages and objections concerning both approaches are extensively discussed. It allows us to draw some more general conclusions on the necessary improvements which should be accounted for in the stochastic modeling of the fatigue crack growth.